Physiological separation of erythrocytes in aortic arch - M. A. Medvedev; G. S. Koval; N. V. Ryazantseva (Бюллетень сибирской медицины, 2007)
The erythrocyte distribution at the level of aortic arch is determined experimentally from structural-functional features. It is shown that there exists the mechanism of physiological separation of erythrocytes, which causes the prevalent income of younger and functionally valid forms of erythrocytes to brain and favors better oxygen supply of nerve cells.